2011
DOI: 10.1103/physreve.83.021801
|View full text |Cite|
|
Sign up to set email alerts
|

Distributions of glass-transition temperature and thermal expansivity in multilayered polystyrene thin films studied by neutron reflectivity

Abstract: We performed neutron reflectivity measurements on multilayered polymer thin films consisting of alternatively stacked deuterated polystyrene (d-PS) and hydrogenated polystyrene (h-PS) layers ∼200 Å thick as a function of temperature covering the glass-transition temperature T(g), and we found a wide distribution of T(g) as well as a distribution of the thermal expansivity α within the thin films, implying the dynamic heterogeneity of the thin films along the depth direction. The reported anomalous film thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 30 publications
5
49
1
Order By: Relevance
“…Recently Kanaya et al made further LEM measurements on PS samples in the form of thin multilayer dPS/hPS films, measured using the longitudinal field (LF) configuration [13]. These results confirmed the presence of the reduction of T g near the surface and provided good consistency with neutron reflectivity measurements made on the same samples [14].…”
Section: Introductionsupporting
confidence: 70%
“…Recently Kanaya et al made further LEM measurements on PS samples in the form of thin multilayer dPS/hPS films, measured using the longitudinal field (LF) configuration [13]. These results confirmed the presence of the reduction of T g near the surface and provided good consistency with neutron reflectivity measurements made on the same samples [14].…”
Section: Introductionsupporting
confidence: 70%
“…Although most applications are in dry environments, analysis of PMMA films in aqueous solutions is of relevance because of their potential as coatings for various types of medical implants [5][6][7] and general use in other applications where protective surface coatings in aqueous solution are required. Studying PMMA films in situ in aqueous solutions is challenging, but neutron reflectometry has been previously used in various studies which characterise thin films of hydrated polymers prepared via spin-coating, in particular with studies of glass transition temperature (T G ) [11,12] and solvent retention [13,14]. Formation of blisters in PMMA [8] films in aqueous solution have been observed with AFM and optical microscopy, where it was suggested that deformation depends on film thickness and Young's modulus of PMMA.…”
Section: Introductionmentioning
confidence: 97%
“…With some exceptions [1], studies of confined polymers have revealed large deviations in properties, e.g., glass transition temperature (T g ), compared with bulk behavior [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Supported films of linear polymers without attractive polymer-substrate interaction report a reduced T g relative to bulk T g (T g;bulk ) upon confinement [2][3][4][5][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…Supported films of linear polymers without attractive polymer-substrate interaction report a reduced T g relative to bulk T g (T g;bulk ) upon confinement [2][3][4][5][7][8][9][10][11][12][13][14]. For example, the seminal 1994 study by Keddie et al [2] revealed that T g À T g;bulk ¼ $ À 24 C for a 17-nm-thick polystyrene (PS) film on silica.…”
mentioning
confidence: 99%
See 1 more Smart Citation